Impact of Sugars on Hypothalamic Satiety Pathways and Its Contribution to Dysmetabolic States - Adriana M. Capucho; Silvia V. Conde (Diabetology, 2022)
Food behaviour is a complex and multifaceted cooperation between physiologic, psychological, social, and genetic factors, influencing meal timing, amount of food intake, food preferences, and food selections. Deregulation of the neurobiological mechanisms controlling food behaviour underlies the development of obesity and type 2 diabetes, two epidemics of the present century. Several brain nuclei are involved in the regulation of the different components of food behaviours; the hypothalamus is the key in controlling appetite and energy homeostasis. In this review, we will explain the role of the hypothalamus in the control of food intake and its interplay with other brain nuclei important in food behaviour. We will also highlight the deregulation of satiety pathways in type 2 diabetes and obesity and the mechanisms behind this deregulation. Finally, knowing that there are different categories of sugars and that they differently impact food behaviours, we will review in a concise manner the studies referring to the effects of sugars in satiety and reward pathways and their impacts on metabolic diseases.